SIMILARITIES OF ELDERLY AND THERAPY-RELATED AML - D’Alò, Francesco; Fianchi, Luana; Fabiani, Emiliano; Criscuolo, Marianna; Greco, Mariangela; Guidi, Francesco; Pagano, Livio; Leone, Giuseppe; Voso, Maria Teresa (Mediterranean Journal of Hematology and Infectious Diseases, 2011)
Acute myeloid leukemia (AML) is a clonal disorder of the hematopoietic stem cell, typical of the elderly, with a median age of over 60 years at diagnosis. In AML, older age is one of the strongest independent adverse prognostic factor, associated with decreased complete response rate, worse disease-free and overall survival, with highest rates of treatment related mortality, resistant disease and relapse, compared to younger patients. While clinical risk factors do not significantly differ between older and younger patients, outcomes are compromised in elderly patients not only by increased comorbidities and susceptibility to toxicity from therapy, but it is now recognized that elderly AML represents a biologically distinct disease, that is itself more aggressive and less responsive to therapy. In elderly individuals prolonged exposure to environmental carcinogens may be the basis for the aggressive biology of the disease. This may also be the basis for similarities between elderly AML and therapy-related myeloid malignancies, mimicking toxic effects of previous cytotoxic treatments on hematopoietic stem cells. Age is itself a risk factor for t-MN, which are more frequent in elderly patients, where also a shorter latency between treatment of primary tumor and t-MN has been reported. Similarities between therapy-related malignancies and elderly AML include morphological aspects, as the presence of multilineage dysplasia preceding and/or concomitant to the development of leukemia, and adverse cytogenetics, including poor karyotype and chromosome 5 and/or 7 abnormalities. Looking at molecular prognosticators in elderly AML, similar to t-MN, reduced frequency of favorable factors, as reduced number of NPM1 and CEBPA mutated cases has been observed, together with increased incidence of negative factors, as increased MDR1 expression, accelerated telomere shortening and frequency of methylation changes. Given the unfavorable prognosis of elderly and t-MN and the similar clinical and molecular aspects, this is a promising field for implementation of new treatment protocols including alternative biological drugs.